The clinical profile of cerebral small vessel disease: Toward an evidence‐based identification of cognitive markers. Issue 1 (31st March 2022) - Salvadori, Emilia; Brambilla, Michela; Maestri, Giorgia; Nicotra, Alessia; Cova, Ilaria; Pomati, Simone; Pantoni, Leonardo
Abstract: There is no consensus on which test is more suited to outline the cognitive deficits of cerebral small vessel disease (cSVD) patients. We explored the ability of eight cognitive tests, selected in a previous systematic review as the most commonly used in this population, to differentiate among cSVD patients, controls, and other dementing conditions performing a meta‐analysis of 86 studies. We found that cSVD patients performed worse than healthy controls in all tests while data on the comparison to neurodegenerative diseases were limited. We outlined a lack of data on these tests' accuracy on the diagnosis. Cognitive tests measuring processing speed were those mostly associated with neuroimaging cSVD markers. There is currently incomplete evidence that a single test could differentiate cSVD patients with cognitive decline from other dementing diseases. We make preliminary proposals on possible strategies to gain information about the clinical definition of cSVD that currently remains a neuroimaging‐based one.